Legal arguments used in courts regarding territoriality and cross-border production orders: From Yahoo Belgium to Microsoft Ireland - de Hert, Paul; Parlar, Cihan; Thumfart, Johannes (New journal of European criminal law, 2018)
This contribution reflects on recent cases involving cross-border data production orders such as Yahoo Belgium, Skype Belgium and Microsoft Ireland. Cross-border data production orders are found to generally involve conflicts regarding sovereignty and enforcement jurisdiction and to frequently include voluntary cooperation of companies for which the legal framework is lacking (Introduction). The Lotus principle, which recognizes a broad extraterritorial jurisdiction to prescribe and limits extraterritorial enforcement jurisdiction, is reconsidered concerning those issues (see the ‘International law pragmatism for jurisdiction to prescribe, but not for jurisdiction to enforce’ section) and the use of mutual legal assistances, which should be the rule, is discussed with four caveats (see the ‘Four caveats to territorial sovereignty and the need for MLAs: Unclarities and politics’ section). Twelve typical arguments are identified, which are employed in courtrooms when cross-border data production orders are discussed, for example, arguments regarding territorial sovereignty, the location of servers, the virtual presence of businesses via the Internet or the nationality of the data subject (see the ‘Arguments in courtrooms in favour or against informal-based cross-border investigations’ section). Subsequently, from fourth to seventh sections, those arguments are investigated regarding their context in the cases Yahoo! Belgium (2007–2015), Skype Belgium (2012–2017), Microsoft Ireland (2013–2018) and Google in re Search Warrant (2017). Finally, a first step to evaluate and test the strength of those arguments is undertaken (see the ‘Assessing the arguments: From logically weak, to unpractical to law enforcement utilitarianism (give us everything)’ section).